The Effect of Work Discipline and Job Satisfaction on Work Productivity with Work Motivation as a Moderating Variable at the Mataram City Administrative Office - Adi Indra Pratama; Mukmin Suryatni; Akhmad Saufi (Cita Konsultindo Research Center, 2024)
This study aims to examine the effect of Work Discipline and Job Satisfaction on Work Productivity with Work Motivation as a moderating variable at the Kelurahan office in Mataram City. This research uses quantitative methods with a causality associative approach. The sample in this study amounted to 83 villages employees who existed and were scattered in the city of Mataram. Data collection using questionnaires that are distributed online using google form. The data analysis tool used is the structural equation model (SEM) method which is processed using the Smart-PLS application. The results of the research findings show that Work Discipline has a positive and significant effect on Work Productivity, Job Satisfaction has a positive and significant effect on Work Productivity, and Work Motivation is able to moderate the influence of Work Discipline and Job Satisfaction on Work Productivity.